2019
DOI: 10.1155/2019/9896012
|View full text |Cite
|
Sign up to set email alerts
|

Development of Strength for Calcium Aluminate Cement Mortars Blended with GGBS

Abstract: In the present study, the development of strength in different calcium aluminate cement (CAC) mixture mortars with granulated ground blast-furnace slag (GGBS) was investigated. The substitution of GGBS levels was 0, 20, 40, and 60% weight of binder, of which the CAC used in this study naturally contained C2AS clinker as a secondary phase. To activate a hydraulic nature of the phase, in addition to the mineral additive, all specimens were cured at 35 ± 2°C for the first 24 hours and then stored in a 95% humidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
11
0
3
Order By: Relevance
“…The C3A phase is the product of the interaction of three molecules of calcium oxide with one package of aluminum oxide at a temperature ranging from (1200 -1280)C ̊ inside the rotary kiln. Its reaction with water or hydration process is very fast, so the temperature emitted from this reaction is high, and this phase is characterized by high early hardness, and the late hardness is weak (Yang et al, 2019). This phase is called Tri Calcium Aluminate and is found in clinker as a secondary phase (Yang et al, 2019).…”
Section: Aluminous Phase C3amentioning
confidence: 99%
“…The C3A phase is the product of the interaction of three molecules of calcium oxide with one package of aluminum oxide at a temperature ranging from (1200 -1280)C ̊ inside the rotary kiln. Its reaction with water or hydration process is very fast, so the temperature emitted from this reaction is high, and this phase is characterized by high early hardness, and the late hardness is weak (Yang et al, 2019). This phase is called Tri Calcium Aluminate and is found in clinker as a secondary phase (Yang et al, 2019).…”
Section: Aluminous Phase C3amentioning
confidence: 99%
“…In many articles, researchers have considered the possibility of reducing the conversion of cement hydration products by using mineral additives such as blast furnace slag, fly ash, silica fume, metakaolin and zeolite [ 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Replacing part of alumina cement with these mineral additives reduces the heat of hydration and causes a reduction in strength.…”
Section: Introductionmentioning
confidence: 99%
“…Mickiewicza 30, 30−059 Kraków, Poland volume changes and strength reduction. The reactive silica released from these additives enters the hydration process, and the so-called strätlingite phase C 2 ASH 8 is produced [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of both high-calcium aluminate material and the by-products of different origins are discussed from the "environmental footprint" point of view [13,14,18,19]. It has been found that usage of CAC as a component of different dry mixtures demonstrates significant environmental benefits in terms of environmental impact (low CO 2 emission, low energy demand vs. early compressive strength, etc.)…”
Section: Introductionmentioning
confidence: 99%